Prevalence of bovine viral diarrhea virus subspecies among persistently infected positive samples submitted to a diagnostic laboratory from cattle in the United States - Vallejo, Jessie (Kansas State University, 2020)
Bovine viral diarrhea virus (BVDV) is an infectious disease affecting ruminants worldwide. Impacting the respiratory, reproductive, and digestive systems, BVDV remains one of the most economically damaging diseases to cattle producers. Previous phylogenetic analysis has divided the virus into two species, BVDV1 and BVDV2, with three main subspecies circulating in U.S. cattle populations: BVDV1a, BVDV1b, and BVDV2a. The objective of this study was to determine the prevalence of the three subspecies in cattle across the United States. Samples were obtained from various segments of the industry: cow/calf, stocker, feedlot, and dairy. Samples used were from live animals where fresh skin (ear notch) had previously tested positive for persistent infection via antigen capture ELISA (ACE) or immunohistochemistry (IHC). This study was comprised of 1,093 samples from 21 states, with a majority of samples from Kansas, Kentucky, Oklahoma, and Texas. Positive samples were submitted to a university diagnostic laboratory and segregated into three subspecies (BVDV1a, BVDV1b, and BVDV2a) via Reverse-Transcriptase PCR (RT-PCR) by sequencing of the 5′-untranslated region (5′-UTR). 1,000/1,093 samples were confirmed positive by PCR. Of the PCR confirmed samples, the prevalence of subspecies BVDV1b BVDV1a, and BVDV2a was 702/1,000 (70.2%), 44/1000 (4.4%), 178/1000 (17.8%), respectively, with 76/1000 (7.6%) of samples unable to be translated successfully. These findings support previous studies exhibiting BVDV1b as the most predominant subspecies among cattle, persistently infected with bovine viral diarrhea virus, in the United States.
Keywords: bovine viral diarrhea; BVD; persistent infection; prevalence; beef cattle; BVDv